Development of advanced three-dimensional tumour models for anti-cancer drug testing - Wan, X (2014)
Animal testing is still the common method to test the efficacy of new drugs, but tissue engineered in vitro models are becoming more acceptable for replacing and reducing animal testing in anti-cancer drug screening by developing in vitro three-dimensional (3D) tumour models for anti-cancer drug testing. In this study, three-dimensional (3D) culture methods were developed to mimic the tumour microenvironment. 3D culturing is to seed, maintain and expand cultured cells in three-dimensional space, in contrast to the traditional two-dimensional (2D) method in which the cells attach to the bottom of culture containers as monolayers. To mimic the intercellular interplay for tumour study, cell co-culture was applied. In this thesis, perfusion culture showed a better homeostasis for 3D tumour model growth over 17 days, with a more controllable working platform and a more reliable response-dose correlation for data interpretation. In the Matrigel sandwich system, the co-culture of breast cancer cells and endothelial cells demonstrated the morphology featuring a vascular network and tumour structures, with the thickness of the three-dimensional structure around 100µm and tubule length 200-400 µm, and maintained for 10 days. The comparisons studies between Matrigel sandwich and other methods suggest that though not fully characterised, Matrigel is still a valuable scaffold choice for developing co-culture 3D tumour model. Finally, the combination of perfusion and co-culture showed the potential of applying this model in angiogenesis assay, with a drug response profile combining cell viability and morphology to mimic in vivo tumour physiology.